2013
DOI: 10.1002/grl.50460
|View full text |Cite
|
Sign up to set email alerts
|

Aragonite saturation state dynamics in a coastal upwelling zone

Abstract: [1] Coastal upwelling zones may be at enhanced risk from ocean acidification as upwelling brings low aragonite saturation state (Ω Ar ) waters to the surface that are further suppressed by anthropogenic CO 2 . Ω Ar was calculated with pH, pCO 2 , and salinity-derived alkalinity time series data from autonomous pH and pCO 2 instruments moored on the Oregon shelf and shelf break during different seasons from 2007 to 2011. Surface Ω Ar values ranged between 0.66 AE 0.04 and 3.9 AE 0.04 compared to an estimated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
149
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 52 publications
8
149
0
Order By: Relevance
“…High-latitude areas of the open ocean will be the most affected by OA owing to the high solubility of CO 2 in cold waters [8][9][10]; however, the California Current Ecosystem (CCE) is already experiencing CO 2 concentrations similar to the projections for high-latitude regions, pointing towards enhanced vulnerability to OA [11][12][13][14]. This is, in part, owing to the natural process of upwelling, which brings already CO 2 -rich waters from the ocean interior to the shelf environment and adds to the anthropogenic CO 2 contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-latitude areas of the open ocean will be the most affected by OA owing to the high solubility of CO 2 in cold waters [8][9][10]; however, the California Current Ecosystem (CCE) is already experiencing CO 2 concentrations similar to the projections for high-latitude regions, pointing towards enhanced vulnerability to OA [11][12][13][14]. This is, in part, owing to the natural process of upwelling, which brings already CO 2 -rich waters from the ocean interior to the shelf environment and adds to the anthropogenic CO 2 contribution.…”
Section: Introductionmentioning
confidence: 99%
“…This is, in part, owing to the natural process of upwelling, which brings already CO 2 -rich waters from the ocean interior to the shelf environment and adds to the anthropogenic CO 2 contribution. These combined processes result in the greater frequency of thermodynamically unfavourable conditions [14,15], enhancing dissolution of CaCO 3 in the water column [16]. The term that quantifies the thermodynamic tendency towards dissolution or precipitation is the saturation state, or V ar (omega); for a given CaCO 3 mineral, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Surface waters of the CCLME already show CO 2 values that can be three times higher than the current global mean (~1200 µatm versus ~4 00 µatm; Harris et al, 2013) due to the upwelling of CO 2 -rich waters. Over recent decades, conditions corrosive to calcified marine organisms have increased in frequency, severity, duration, and spatial extent (Feely et al, 2008;Harris et al, 2013) Moreover, changes observed in the ocean today do not reflect the full amount of anthropogenic CO 2 already in the atmosphere, because ocean circulation imposes decadal-scale time lags between CO 2 uptake at the ocean surface and subsequent upwelling of deeper CO 2 -enriched waters (Feely et al, 2008) Even if today's atmospheric CO 2 levels were stabilized, acidification would further intensify over the coming decades, reflecting increases in atmospheric CO 2 concentrations that have occurred over the past decades.…”
Section: Oah In the California Current Large Marine Ecosystemmentioning
confidence: 92%
“…Some MPAs may be especially vulnerable to ecological disruption if they are exposed to local environmental stressors; for example, some areas along the Oregon coast periodically experience fish and invertebrate mortality during hypoxic events (Chan et al, 2008) and appear particularly susceptible to acidification (Harris et al, 2013). Going forward, designation of new MPAs and refinements to existing MPA networks will require consideration of current and future OAH conditions.…”
Section: Coastal Managementmentioning
confidence: 99%
See 1 more Smart Citation